KERJASAMA PENGELOLAAN KEBUN (MUKHABARAH) DAN DAMPAKNYA TERHADAP PENDAPATAN MASYARAKAT DESA KERTOPATI - M. Darul Qutni; A.A Miftah; Nurfitri Martaliah (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2024)
This research aims to determine cooperation in agricultural land management and its impact on the income of the Kertopati Village community. This research is qualitative type using primary and secondary data sources. The object of this research is a number of communities who collaborate with . Data was obtained directly from respondents by carrying out data analysis methods, namely observation, interviews and personal documentation, then the data was processed using data processing techniques. The results of the research show that: That the mechanism for implementing cooperation in managing gardens uses the Mukhabarah agreement in Kertopati Village, which has two mechanisms for carrying out cooperation with the Mukhabarah agreement or profit sharing system. Then the profit sharing or Bagi due hasil system is able to provide welfare to people who do not own land at all but have capital. And the people of Kertopati Village who work as farmers have carried out Bagi due hasil in accordance with the Mukhrabah agreement indirectly, because they initially knew that the systems in the Bagi due hasil process were part of the application of customs but had been synchronized by religious leaders in accordance with views in the Islamic religion.